Enhancing fracture toughness of polymer‐based functional energetic composites by filling nano‐graphene in matrix. (6th May 2018) - Li, Yubin; Yang, Zhijian; Liu, Jiahui; Lin, Congmei; Zhang, Jianhu; Zheng, Xue
Abstract : With the emergence and commercialization of graphene, new opportunities have emerged for toughening polymer‐based functional energetic composites (e.g., polymer‐bonded explosives [PBX]) using nano‐graphene without sacrificing strength and glass transition temperature, as compared with conventional elastomeric tougheners. In this work, inorganic nano‐graphene is used to study the toughness enhancing effects and mechanical properties of 1, 3, 5, 7‐tetranitro‐1, 3, 5, 7‐tetrazocane (HMX)‐based PBX. Fabrication procedures of HMX‐based PBX with different content of graphene are presented, and well‐dispersion for graphene in binder matrix is obtained by ultrasonic processing. Experimental results indicated the addition of nano‐graphene can greatly increase the toughness, with the fracture energy enhanced from 32.5 to 64.9 J m −3 compared with normal HMX‐based PBX. Such improvement was obtained at a low graphene concentration (0.2–0.4 wt%). Strong interaction of the graphene and the binder matrix, combined with the inherent properties of well‐dispersed graphene are the decisive factors with respect to the outstanding toughening effect. POLYM. COMPOS., 40:E1151–E1161, 2019. © 2018 Society of Plastics Engineers